Validation of Strasbourg environmental exposure chamber (EEC) ALYATEC® in mite allergic subjects with asthma - Khayath, Naji; Doyen, Virginie; Gherasim, Alina; Radu, Carmen; Choual, Ibrahim; Beck, Nicole; Jacob, Audrey; Schoettel, Florian; Vecellio, Laurent; Domis, Nathalie; de Blay, Frédéric (The Journal of asthma, 2020)
Objective: Environmental Exposure Chamber (EEC) should have standardized and controlled allergenic and non-allergenic exposures to perform reproducible clinical studies. The aim was to demonstrate that mite exposure in the Alyatec ® EEC could induce early (EAR) and/or late asthmatic reactions (LAR) in at least 60% of subjects allergic to mite. Methods: The EEC has a volume of 147-m 3 with 20 seats. The nebulized particle number, airborne Der p1, endotoxins, and volatile organic compound (VOC) concentrations were measured. Twenty-four asthmatics allergic to mite were randomly exposed to 15, 25, and 46 ng/m 3 Der p1. Specificity was assessed in not mite-sensitized asthmatics. Results: No significant endotoxin or VOC contamination was measured. The mean inter-assay CVs were 12.5% for the airborne particle number and 28.7% for airborne Der p1 concentrations. For the three Der p1 concentrations, at least 88% of the subjects developed EAR and/or LAR, and at least 46% developed a dual response. No reaction occurred with placebo or in the control group. No severe bronchial reaction occurred. Conclusions: The Alyatec ® EEC demonstrated a tight control of allergenic and non-allergenic exposures. The EEC was clinically validated, with airborne Der p1 levels close to levels found in natural settings.